Crisis intervention and suicide - Nazari Jeirani (Iran University of Medical Sciences, 1993)
Nursing standards of prevention of suicide in the hospital , is caution s related to suicide . This involves assigning a room with several beds near the nursing station, collecting of dangerous instruments, limiting of each unit, and excessive caring by nurse. The purpose of this policy is preventing of self- destructing behaviors in hospital. However these interventions are not effective unless the suicidal thoughts away from patient in the hospital and after discharge. Studies showed that in the first three months after discharge the risk of suicide will be increased.